Prevalence of Buxtonella sulcata Infection in Bovines of Southern Haryana - S, Jinu Manoj; Singh, Manoj Kumar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Buxtonella sulcata is considered as an opportunistic ciliate protozoan inhabiting the large intestine especially the colon of bovines. In this study, the prevalence of B. sulcata in bovines of southern Haryana is reported according to season, age and health statusof animals. Coprological examination of faecal samples from cattle and buffaloes for B. sulcata revealed a prevalence rate of 25.69% and 34.65%, respectively. It was found that the highest prevalence was among heifers (52.90% and 33.84%), followed by calves(29.28% and 25.71%) and adults (8.69% and 13.63%) in both the species. The prevalence of this protozoan infection among diarrhoeic buffaloes and cattle were found as 38.18% and 31.57%, respectively with a statistical significance (p